2023
DOI: 10.1111/gbb.12862
|View full text |Cite
|
Sign up to set email alerts
|

The collaborative study on the genetics of alcoholism: Brain function

Jacquelyn L. Meyers,
Sarah J. Brislin,
Chella Kamarajan
et al.

Abstract: Alcohol use disorder (AUD) and related health conditions result from a complex interaction of genetic, neural and environmental factors, with differential impacts across the lifespan. From its inception, the Collaborative Study on the Genetics of Alcoholism (COGA) has focused on the importance of brain function as it relates to the risk and consequences of alcohol use and AUD, through the examination of noninvasively recorded brain electrical activity and neuropsychological tests. COGA's sophisticated neurophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 163 publications
0
6
0
Order By: Relevance
“…COGA includes EEG-derived event-related oscillation (ERO) response measures . Prior studies have found the P300 component during the standard visual oddball paradigm to be associated with family history of AUD .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…COGA includes EEG-derived event-related oscillation (ERO) response measures . Prior studies have found the P300 component during the standard visual oddball paradigm to be associated with family history of AUD .…”
Section: Methodsmentioning
confidence: 99%
“…COGA includes EEG-derived event-related oscillation (ERO) response measures . Prior studies have found the P300 component during the standard visual oddball paradigm to be associated with family history of AUD . Subgroup differences for parietal delta (1-3 Hz) and frontal theta (3-7 Hz) band EROs (300-700 millisecond window) and parietal P300 amplitude were also included as correlates of AUD severity in cross-sectional analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG recording and processing have been detailed previously (Meyers et al, 2023). Briefly, resting (eyes-closed) EEG was recorded for 4.25 min; a continuous interval of 256 seconds was analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…COGA brought together investigators across disciplines, all who share the goal of understanding both biological and environmental risk factors for AUDs and possible treatments. This issue includes five articles describing the work spanning three decades, which is broadly reviewed in four areas: sample and clinical data, 1 brain function, 2 genetics 3 and functional genomics, 4 with an introductory overview. 5 The COGA study exemplifies elegance in its ability to apply creative ideas, innovative approaches, critical thinking and patience while working within a framework of collaborative science.…”
mentioning
confidence: 99%